To Investigate Leucas Cephalotes For Its Antioxidant And Hepatoprotective Activity Against Ccl4 Induced Hepatotoxicity In Swiss Albino Mice - ITORIA PRIYANK; JAIN GAURAV (International Journal of Pharma and Bio Sciences, 2012)
Leucas cephalotes is a weed flora of wet season and has been traditionally used as mild stimulant, diaphoretic and used in fever and liver disorder. The object of the present study is to investigate the methanolic extract of the plant Leacus Cephalotes for hepatoprotective activity against carbon tetra chloride-induced liver damage in swiss albino mice and antioxidant activity by hydrogen peroxide scavenging assay in dose dependant manner. Methanolic extract of plant Leacus cephalotes investigate for hepatoprotective activity against carbon tetrachloride induced hepatotoxicity using biochemical markers Serum glutamate pyruvate transaminase- SGPT, Serum glutamate oxaloacetate transaminase- SGOT, serum bilirubin, Serum alkaline phosphatase- SALP. The hepatoprotective activity was also supported by histopathological studies of liver tissue. Antioxidant activity investigated by invitro hydrogen peroxide scavenging assay. Biochemical studies of blood samples of methanolic extract of Leacus Cephalotes showed significant decrease in the levels of serum markers, indicating the protection of hepatic cells, the extract of above plant could afford significant protection against CCl4 induced hepatocellular injury. The methanolic extract from Leucas cephalotes exerts significant antioxidant effects, which were comparable with standard drugs. Administration of methanolic extract of the plant Leacus Cephalotes protect the liver from toxic effects of carbon tetra chloride by reducing the elevated levels of Serum enzymes which shows the significant protection against CCl4 induced hepatocellular injury.